فاعلية برنامج مقترح لعلاج صعوبات تعلم القراءة لدى تلاميذ الصف السادس بمرحلة التعليم الأساسي بمدينة مصراتة (Journal of Academic Research, 2026)
The study aimed to examine the effectiveness of a proposed program for treating reading difficulties among sixthgrade students in basic education in Misrata. It followed an experimental method with a control group (1 7 students) and an experimental group (1 7 students), selected purposively from a total of 80 students from Raba Al-adaweya school. The researcher used diagnostic tools and a pre- and post-reading test, then applied the program to the experimental group. The results showed statistically significant differences in favor of the experimental group in the post-test.The study recommended strengthening the teacher's role in identifying learning difficulties and implementing appropriate programs using proper diagnostic tools and training.